2020
DOI: 10.1002/pei3.10009
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of a high CO2 future on leguminous species

Abstract: The Leguminosae family comprises approximately 800 genera and 20,000 species, and constitutes the third largest family of flowering plants (Stagnari et al., 2017). In terms of agronomically important crops, grain legumes (pulses), soybean, and certain forage species (e.g., alfalfa [Medicago sativa]) provide value as both food and feed due to their high levels of protein and health-promoting properties (Darmadi-Blackberry et al., 2004; Graham & Vance, 2003; Singh et al., 2017). In addition, their capacity to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 235 publications
(448 reference statements)
1
6
0
Order By: Relevance
“…Similar findings where a leguminous plant attained more biomass than nonleguminous plant grown at eCO 2 were reported by Lee et al (2003). Moreover, Singer et al (2020) reported that leguminous species have a close relationship with arbuscular mycorrhizal fungi which promotes efficient uptake of P, in turn increasing biomass of leguminous trees. In addition, increase in nodule mass in legumes which is non-existent in non-leguminous trees could have contributed to the total biomass production of legumes.…”
Section: Influence Of Woody Plant Functional Traits On Responses To Ecosupporting
confidence: 82%
See 4 more Smart Citations
“…Similar findings where a leguminous plant attained more biomass than nonleguminous plant grown at eCO 2 were reported by Lee et al (2003). Moreover, Singer et al (2020) reported that leguminous species have a close relationship with arbuscular mycorrhizal fungi which promotes efficient uptake of P, in turn increasing biomass of leguminous trees. In addition, increase in nodule mass in legumes which is non-existent in non-leguminous trees could have contributed to the total biomass production of legumes.…”
Section: Influence Of Woody Plant Functional Traits On Responses To Ecosupporting
confidence: 82%
“…Indeed, many short-term studies have reported an increase in C assimilation and a subsequent increase in photosynthesis under saturating light and elevated CO 2 (eCO 2 ), more so for C 3 species relative to their C 4 counterparts (Zhang et al 2021;Raubenheimer and Ripley 2022). This is driven mainly by the fact that C 3 photosynthesis does not saturate at current levels of CO 2 (Singer et al 2020). High CO 2 uptake not only increases shoot growth and biomass, but also root depth and biomass, which further promotes soil nutrient and water uptake, indirectly enhancing photosynthesis (Thompson et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations